Activation of α2A‐containing nicotinic acetylcholine receptors mediates nicotine‐induced motor output in embryonic zebrafish. (17th April 2014) - Menelaou, Evdokia; Udvadia, Ava J.; Tanguay, Robert L.; Svoboda, Kurt R.
Abstract It is well established that cholinergic signaling has critical roles during central nervous system development. In physiological and behavioral studies, activation of nicotinic acetylcholine receptors (nAChRs) has been implicated in mediating cholinergic signaling. In developing spinal cord, cholinergic transmission is associated with neural circuits responsible for producing locomotor behaviors. In this study, we investigated the expression pattern of the α2A nAChR subunit as previous evidence suggested it could be expressed by spinal neurons. In situ hybridization and immunohistochemistry revealed that the α2A nAChR subunits are expressed in spinal Rohon–Beard (RB) neurons and olfactory sensory neurons in young embryos. To examine the functional role of the α2A nAChR subunit during embryogenesis, we blocked its expression using antisense modified oligonucleotides. Blocking the expression of α2A nAChR subunits had no effect on spontaneous motor activity. However, it did alter the embryonic nicotine‐induced motor output. This reduction in motor activity was not accompanied by defects in neuronal and muscle elements associated with the motor output. Moreover, the anatomy and functionality of RB neurons was normal even in the absence of the α2A nAChR subunit. Thus, we propose that α2A‐containing nAChRs are dispensable for normal RB development. However, in the context of nicotine‐induced motor output, α2A‐containing nAChRs on RB neurons provide the substrate that nicotine acts upon to induce the motor output. These findings also indicate that functional neuronal nAChRs are present within spinal cord at the time when locomotor output in zebrafish first begins to manifest itself.